Effect of the exposure to Mn-doped ZnS nanoparticles on biomarkers in the freshwater western mosquitofish Gambusia affinis. Issue 1 (2nd January 2019) - Touaylia, Samir; Labiadh, Houcine
ABSTRACT: Synthesized Mn-doped ZnS nanoparticles, with 10% of Mn dopant, were used to investigate their environmental toxicity. Mn-doped ZnS quantum dots (QDs) stabilized by 3-mercaptopropionic acid (MPA) were synthesized in a basic aqueous solution using the nucleation doping. The optical properties and structure of the obtained Mn (10%):ZnS QDs have been characterized by X-ray diffraction, UV–vis, photoluminescence spectroscopies and transmission electron microscopy. The brain, gills and liver stained sections from Gambusia affinis were dissected. Antioxidant enzyme activities (acetylcholinesterase and catalase), as well as malondialdehyde and H2 O2 levels, were determined after exposure (94 h) to 14 and 28 mg/L of nanoparticles. The obtained nearly monodisperse Mn(10%):ZnS@MPA QDs have an average diameter of ca. 2.8 nm and a zinc-blende crystal structure. Mn-doped ZnS acts differently on the activities of the biomarkers in a dose-dependent manner. The recorded alterations varied between organs. Such findings provide information on the biological target of nanoparticles and their behaviour within the environment.